Feminist legal theory : a primer - Levit, Nancy; Verchick, Robert R. M. (New York University Press, 2016)
"Feminist legal theory is one of the most dynamic fields in the law, and it affects issues ranging from child custody to sexual harassment. Since its initial publication in 2006, Feminist Legal Theory: A Primer has received rave reviews. Now, in the completely updated second edition of this outstanding primer, Nancy Levit and Robert R.M. Verchick introduce the diverse strands of feminist legal theory and discuss an array of substantive legal topics, pulling in recent court decisions, new laws, and important shifts in culture and technology. The book centers on feminist legal theories, including equal treatment theory, cultural feminism, dominance theory, critical race feminism, lesbian feminism, postmodern feminism, and ecofeminism. Readers will find new material on women in politics, gender and globalization, and the promise and danger of expanding social media. Updated statistics and empirical analysis appear throughout. The authors, prominent experts in the field, also address feminist legal methods, such as consciousness-raising and storytelling. The primer offers an accessible and pragmatic approach to feminist legal theory. It demonstrates the ways feminist legal theory operates in real-life contexts, including domestic violence, reproductive rights, workplace discrimination, education, sports, pornography, and global issues of gender. The authors highlight a sweeping range of cutting-edge topics at the intersection of law and gender, such as single-sex schools, abortion, same-sex marriage, rape on college campuses, and international trafficking in women and girls. At its core, Feminist Legal Theory shows the importance of the roles of law and feminist legal theory in shaping contemporary gender issues."--